Determination of the packaging requirements and storage stability of turon de casoy - Mutuc, Noel Santos; Mateo, Liwayway T. (1992.)
The study was undertaken with the main objective of determining the packaging requirements and storage stability of turron de casuy. In the first phase, the sorption isotherm of the product was determined using the Direct Hygrometric Method. The resulting curve showed that the product is most stable between 25% and 38% relative humidity conditions. Maximum hygroscopicity of the product tends to develop at relative humidities above 64%. The critical moisture content was found to be 5.30% (dry basis). Based on the sorption isotherm and the critical moisture content, the maximum allowable water vapor transmission rate was calculated to be 0.4618 g/sq.m.-day at 90% gradient and 208°C. two types of packaging materials, namely: HDPE and PP, were selected for the shelf life estimation based on the computed WVTR value. The shelf life values of the product in these packaging materials were calculated using the Half-Value Period Method. Results showed that two of the three packaging materials tested were adequate in meeting the desired shelf life of 6 months under average ambient conditions in the Philippines of 28°C and 81% RH. Both 0.0048 cm. HDPE were found effective in prolonging the product's keeping quality up to 324 days and 364 days, respectively. Only the present packaging of turron de casuy, ie. 0.0051 cm. PP, which gave a shelf life value of 97 days was found inadequate in meeting desired shelf-life. However, 0.0048 cm. HDPE is recommended for use since it costs cheaper than the thicker HDPE. When used together with metal cans, the product's shelf stability is expected to last for a longer period even when stored at extreme conditions.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Turon de casoy -- Packaging; Turon de casoy -- Storage